A High-Continuity Genome Assembly of Chinese Flowering Cabbage (Brassica rapa var. parachinensis) Provides New Insights into Brassica Genome Structure Evolution - Guangguang Li; Ding Jiang; Juntao Wang; Yi Liao; Ting Zhang; Hua Zhang; Xiuchun Dai; Hailong Ren; Changming Chen; Yansong Zheng (Plants, 2023)
Chinese flowering cabbage (Brassica rapa var. parachinensis) is a popular and widely cultivated leaf vegetable crop in Asia. Here, we performed a high quality de novo assembly of the 384 Mb genome of 10 chromosomes of a typical cultivar of Chinese flowering cabbage with an integrated approach using PacBio, Illumina, and Hi-C technology. We modeled 47,598 protein-coding genes in this analysis and annotated 52% (205.9/384) of its genome as repetitive sequences including 17% in DNA transposons and 22% in long terminal retrotransposons (LTRs). Phylogenetic analysis reveals the genome of the Chinese flowering cabbage has a closer evolutionary relationship with the AA diploid progenitor of the allotetraploid species, Brassica juncea. Comparative genomic analysis of Brassica species with different subgenome types (A, B and C) reveals that the pericentromeric regions on chromosome 5 and 6 of the AA genome have been significantly expanded compared to the orthologous genomic regions in the BB and CC genomes, largely driven by LTR-retrotransposon amplification. Furthermore, we identified a large number of structural variations (SVs) within the B. rapa lines that could impact coding genes, suggesting the functional significance of SVs on Brassica genome evolution. Overall, our high-quality genome assembly of the Chinese flowering cabbage provides a valuable genetic resource for deciphering the genome evolution of Brassica species and it can potentially serve as the reference genome guiding the molecular breeding practice of B. rapa crops.